2020
DOI: 10.1002/jcla.23317
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs in osteosarcoma via various signaling pathways

Abstract: Osteosarcoma (OS) is one of the most commonly seen malignant bone tumors, which has higher incidence in both children and teenagers with lung metastasis. 1,2 Three main strategies, namely surgical resection, chemotherapy, and radiotherapy are applied for patients currently. 3 Neoadjuvant chemotherapy combined with surgical treatment has been reported to improve the 5-year survival rate to nearly 70% in localized OS over the past three decades, however, chemoresistance to these drugs is still the main obstacle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 96 publications
1
18
0
Order By: Relevance
“…Studies have shown that an increasing number of ncRNAs are associated with tumors 34 - 38 . For example, long non-coding RNAs (lncRNAs) can affect the development and progression of tumors 34 , 35 . Circular RNA can also affect many diseases, including cancers 36 - 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that an increasing number of ncRNAs are associated with tumors 34 - 38 . For example, long non-coding RNAs (lncRNAs) can affect the development and progression of tumors 34 , 35 . Circular RNA can also affect many diseases, including cancers 36 - 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that Chlamydia pneumonia can induce ET-1 production through the MAPK/p38 signaling pathway in vascular smooth muscle cells to promote cell proliferation ( Kern et al, 2009 ). ZFAS1 has been shown to activate MAPK signaling pathway, and promote the migration and invasion of cervical cancer cells by regulating the MAPK/p38 signaling pathway ( Gan et al, 2019 ; Han and Shen, 2020 ). In our experiment, MAPK/p38 activation was repressed during the anti-apoptotic process after interfering ZFAS1 expression, indicating that ZFAS1 can exert an anti-apoptotic effect by regulating the p38 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 90 It has been proved that HOTAIR promotes the proliferation and invasion of OS cells by the AKT/mTOR signaling pathway. 91 However, it is also involved in bone regeneration from MSCs. 4 HOTAIR reduces the expression of miR-17-5p and elevates the Smad7 transcript level at the same time, and thus Smad7 is a target of miR-17-5p .…”
Section: Main Textmentioning
confidence: 99%